Impact of DNA purification method and primer selection on 16S rRNA gene metabarcoding on wine - Francesco Cerutti (OENO One, 2019)
Aim: The high-throughput sequencing methods have revolutionized the study of the microbiota in different matrices including those of the grapevine production chain. DNA extraction is a crucial step in the sample processing. In this study, we compared different DNA purification methods and two primer sets for 16S rRNA gene metabarcoding to evaluate the best protocol to explore the wine microbiota by metabarcoding. Methods and results: We collected a wine from Barbera grapes after malolactic fermentation previously inoculated by Oenococcus oeni starter. The same sample was used to evaluate the best performing protocol to study the wine microbiota. DNA was purified using nine different methods and then amplified for the 16S rRNA gene with two primer sets (according to Illumina or Earth Microbiome Project protocols). The obtained amplicons were then sequenced in a single sequencing session on an Illumina MiSeq. We evaluated the best protocol considering DNA concentration and purity, alpha (Observed species) and beta diversity from metabarcoding analysis. The sequencing generated 36,031,756 reads in total. Although no statistically significant difference was observed between purification methods or primer sets, better results were obtained with phenol-chloroform DNA purification combined to Earth Microbiome Project primers. Metabarcoding was able to highlight the domination of the inoculum, O. oeni, representing the main species of the analyzed wine microbiota. Conclusion: Our data show that, for the tested wine, metabarcoding output is more influenced by the primer set than by the DNA purification method. Moreover, the metabarcoding detected that O. oeni represents the main species, evidencing the domination of the inoculum done with lyophilized commercial preparation of this species. Other lactic acid bacteria are present at a much lower abundance. Significance and impact of the study: This is the first report applying the 16S rRNA gene metabarcoding to study the microbiota of wine. For this reason, the evaluation of alternative methods for DNA processing is essential for future research using this innovative methodology.